Assessment of Mental Well-Being and Coping Strategies Among Employees of Government-Owned and Controlled Corporations (GOCCs) in Catanduanes - Advincula Tadoy, Hyde; Cuevillas, Rowena (JPAIR Multidisciplinary Research, 2026)
Mental well-being has become an urgent global and national concern, particularly in public sector workplaces where employees face increasing occupational stressors. Despite the enactment of Republic Act No. 11036 and related policy mandates, implementation gaps remain evident in Government-Owned and Controlled Corporations (GOCCs), especially in geographically isolated provinces such as Catanduanes. This study aimed to assess the mental well-being of GOCC employees in Catanduanes by examining their socio-demographic profile, identifying common workplace stressors, evaluating coping strategies, assessing the level of implementation of workplace and mandatory programs, and developing a mental health management framework. A descriptive research design was employed, utilizing a structured survey questionnaire administered to purposively selected GOCC employees in the province. Data were analyzed using descriptive statistical techniques. Findings revealed moderate levels of workplace stress, particularly related to workload, leadership practices, job security, and work schedules. Employees reported the use of both problem-focused and emotion-focused coping strategies; however, the implementation of mandated mental health and workplace programs was found to be moderate to limited. The study concludes that a localized, structured Mental Health and Wellness Support Program is necessary to strengthen institutional support systems, enhance employee resilience, and promote a healthier and more productive government workforce.
Keywords: Mental well-being; GOCC employees; workplace stressors; coping strategies; organizational support; Catanduanes; Philippines